Effect of quasi-static pre-strain on electromagnetic forming limits for high strength steel sheets. (2017) - Lei, Yu; Huang, Shangyu; Liu, Wei; Yan, Shiwei; Zhou, Mengcheng; Hu, Jianhua; Zou, Xifan
The forming limits of high strength steel sheets DP590 and B280VK were experimentally investigated at three kinds of strain rates, including quasi-static loading, electromagnetic loading and hybrid loading. For the quasi-static and electromagnetic hybrid loading, the high strength steel sheets with different pre-strain levels at quasi-static loading condition were sequentially deformed by electromagnetic loading. It can be observed that the hybrid electromagnetic forming (EMF) limits of both high strength steel sheets DP590 and B280VK are much higher than those at quasi-static or electromagnetic loading conditions. Meanwhile, the experiment results show that the hybrid EMF limits are affected by the level of quasi-static pre-strain, and the hybrid EMF limits with the quasi-static pre-strain of 2.5% and 7% are higher than those with the largest quasi-static pre-strain of 16%.